Controlled Release of Ropivacaine from Single-Armed (1-PCL) and Four-Armed PCL (4-PCL) Microspheres - Wei Xiong; Yue-kun Shen; Peng Dong; Ying Xiao; Xiong-qing Huang; Wen-qi Huang; Lu Yang; Xia Feng (International Journal of Polymer Science)
Sustained release of anesthesia has shown great promise in the treatment of chronic pain in patients. In this research, we used neutralized ropivacaine as an anesthesia and poly(ε-caprolactone) (PCL) with different architectures to systematically study how these architectures affect the release of ropivacaine. After optimizing the parameters of the preparation of microspheres, ropivacaine-loaded 1-PCL microspheres and 4-PCL microspheres were obtained. Fourier Transform infrared spectra (FT-IR) and X-ray diffraction spectra (XRD) confirmed that ropivacaine was encapsulated within the microsphere rather than inserted on the surface of the microsphere. Ropivacaine was found to be buried deeper in the 1-PCL microsphere than in the 4-PCL microsphere. In vitro release assay revealed that small crystalline grains interfered with ropivacaine release in 4-PCL microspheres during the initial release period, but then two kinds of microspheres showed a similar ropivacaine release rate. We basically proved that the architecture of PCL has a negligible effect on ropivacaine release. Cell proliferation test revealed that the release of products from the microspheres resulted in insignificant toxicity towards mammalian cells.